Assessment of the Origins and Spread of Putative Resistance-Conferring Mutations in Plasmodium vivax Dihydropteroate Synthase (2009)
ABSTRACT: Infection with Plasmodium vivax is usually treated with chloroquine, but parasites are often exposed inadvertently to sulfadoxine-pyrimethamine. To infer patterns of selection and spread of resistant parasites in natural populations, we determined haplotypes of P. vivax dihydropteroate synthase ( dhps ) alleles that could confer resistance to sulfadoxine. We amplified the P. vivax pyrophosphokinase ( pppk )– dhps region and its flanking intergenic regions from 92 contemporary global isolates. Introns and exons of pppk-dhps were highly polymorphic, as were the flanking intergenic regions. Eighteen haplotypes were associated with wild-type alleles, but several different putatively sulfadoxine-resistant alleles have arisen in areas of intensive sulfadoxine-pyrimethamine use. Even when they encoded changes to the same amino acid, these mutant alleles were associated with multiple different haplotypes. Two main conclusions can be drawn from these data. First, dhps alleles resistant to sulfadoxine have arisen multiple times under drug pressure. Second, there has been convergent evolution of a variety of alleles that could confer resistance to sulfa drugs.